2022
DOI: 10.1001/jamaoto.2022.2285
|View full text |Cite
|
Sign up to set email alerts
|

Improved Inflammatory and Cardiometabolic Profile After Soft-Tissue Sleep Surgery for Obstructive Sleep Apnea

Abstract: ImportanceObstructive sleep apnea (OSA) is associated with a rise in serum inflammatory markers, which may be attenuated by sleep surgery.ObjectiveTo evaluate whether sleep surgery was associated with improved levels of proinflammatory markers in adults with OSA.Data SourcesTwo authors independently searched Cochrane, Embase, and PubMed databases from inception through June 14, 2022.Study SelectionTwo authors searched the Cochrane, Embase, and PubMed databases for studies comparing preoperative and postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It would be worthwhile to increase the number of biological replicates in mice to fully characterize the conserved signature between mice and humans. TNF-α has been described in various inflammatory diseases including NASH and OSA 31 , 32 , 33 while little is known about IL20 and LIF in these pathologies. 34 IL20 has been implicated in several inflammatory diseases 35 and ongoing clinical trials are investigating the potential therapeutic effects of anti-IL20 in psoriasis and rheumatoid arthritis (NCT01038674, NCT01261767) making IL20 an interesting target to explore in the context of OSA and NASH.…”
Section: Discussionmentioning
confidence: 99%
“…It would be worthwhile to increase the number of biological replicates in mice to fully characterize the conserved signature between mice and humans. TNF-α has been described in various inflammatory diseases including NASH and OSA 31 , 32 , 33 while little is known about IL20 and LIF in these pathologies. 34 IL20 has been implicated in several inflammatory diseases 35 and ongoing clinical trials are investigating the potential therapeutic effects of anti-IL20 in psoriasis and rheumatoid arthritis (NCT01038674, NCT01261767) making IL20 an interesting target to explore in the context of OSA and NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory markers including CRP are increased in OSA [ 91 ] and inflammatory (CRP, IL-6, and TNF-α) and cardiometabolic profiles (total cholesterol, LDL, triglyceride) as well as leptin are improved following soft-tissue surgery for OSA [ 92 ]. Likewise, the neutrophil-to-lymphocyte ratio (NLR), a measure of subclinical systemic inflammation, is significantly reduced in patients using CPAP [ 93 ].…”
Section: Treatment For Osa and Cvd Riskmentioning
confidence: 99%
“…Numerous studies have reported postoperative improvement of such clinical outcomes as symptoms, cardiovascular risk, quality of life, and mortality [10]. However, except for some primary candidates for surgery and a few surgical procedures, such as MMA or tracheostomy, most surgical procedures for OSA are generally not recognized as curative treatments, because the possibility of cure is relatively low and the outcome after surgery is difficult to predict [2,7,9].…”
Section: Outcomes Of Obstructive Sleep Apnea Surgery In Korea Surgica...mentioning
confidence: 99%